Puritanism from the Outside - Alan Ford (Revue Française de Civilisation Britannique)
Puritanism has, rightly, been seen as a primarily English phenomenon. But puritan ideas can also be studied in very different contexts, as they spread throughout the English-speaking religious world. This article seeks to “decentre” puritanism by examining it from the perspective of the other two national churches in Britain and Ireland – those in Scotland and Ireland. Taking Patrick Collinson’s definition of puritanism—that it was not something definable in itself, but rather it was one half of a stressful relationship – it is shown that in both Ireland and Scotland, puritanism only came into existence when it was attacked by the English monarch and by those who saw puritanism in terms of its English manifestation. Until well into the seventeenth century, puritanism in both Ireland and Scotland was just a largely unnoticed part of a broadly reformed church. Only with the extension of royal power in the course of the first half of the seventeenth century, and the subsequent determination of King Charles I and Archbishop William Laud to bring the three Churches into closer conformity, did puritanism become a major issue in Ireland and Scotland.